Face-booking to perfection : an exploration of the dynamics that exist between the online and offline self. - Thambusamy, Gayathiri. (2013)
Despite Facebook’s explosive popularity in Singapore there has been a paucity of sociological research that highlights the dynamics inherent within this Social Networking Site. There is also a lack of research, in Singapore, that sheds light on the increasing interconnectivity of social networking sites and the lives of Singaporeans. Being an avid user of Facebook, I have noticed how Facebook is intertwined with my life as well as youngsters who belong to my age group This study would explore the dynamics that exists between the Facebook self (online self) and the offline self. More specifically the study would seek to understand if the undergraduates feel that there exists a difference between their offline and online self. It would also explore the possible reasons that lead to this difference, if any.